2001
DOI: 10.1046/j.1365-2885.2001.00307.x
|View full text |Cite
|
Sign up to set email alerts
|

Inadequacy of low‐volume resuscitation with hemoglobin‐based oxygen carrier hemoglobin glutamer‐200 (bovine) in canine hypovolemia

Abstract: Stroma-free hemoglobin-based oxygen carriers (HBOC) have been developed to overcome problems associated with transfusion of allogeneic blood. We have studied the efficacy of the first licensed veterinary blood substitute, hemoglobin glutamer-200 bovine (Oxyglobin; Biopure, Cambridge, MA, USA, Hb-200), in a canine model of acute hypovolemia and examined whether clinically commonly used criteria are adequate to guide fluid resuscitation with this product. Twelve anesthetized dogs were instrumented for measuremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
0
3

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(58 citation statements)
references
References 46 publications
3
52
0
3
Order By: Relevance
“…It shares most properties with Hb glutamer-250 (bovine; Hemopure [formerly HBOC-201], Biopure) (7), which is currently in phase III clinical trials and approved for use in humans in South Africa. Previous studies with low doses of Hb-200 (8,9) and HBOC-201 (10) revealed an improvement of hemodynamic functions, yet a significantly smaller increase in arterial oxygen content and oxygen delivery after HBOC infusion than expected based on the amount of Hb administered. Therefore, in the present study, our primary goal was to analyze whether infusion of Hb-200 will dosedependently and to a greater extent than conventional plasma expanders increase systemic oxygen delivery and tissue oxygenation in dogs subject to isovolemic resuscitation after acute blood loss.…”
mentioning
confidence: 82%
See 2 more Smart Citations
“…It shares most properties with Hb glutamer-250 (bovine; Hemopure [formerly HBOC-201], Biopure) (7), which is currently in phase III clinical trials and approved for use in humans in South Africa. Previous studies with low doses of Hb-200 (8,9) and HBOC-201 (10) revealed an improvement of hemodynamic functions, yet a significantly smaller increase in arterial oxygen content and oxygen delivery after HBOC infusion than expected based on the amount of Hb administered. Therefore, in the present study, our primary goal was to analyze whether infusion of Hb-200 will dosedependently and to a greater extent than conventional plasma expanders increase systemic oxygen delivery and tissue oxygenation in dogs subject to isovolemic resuscitation after acute blood loss.…”
mentioning
confidence: 82%
“…Methods were essentially as described and discussed in detail previously (8,9) with modifications mentioned below.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A esplenectomia foi realizada como medida complementar para anular o efeito da espleno-contração na fase compensatória do choque, sendo que, em cães, este órgão pode contribuir, durante esta fase, liberando sangue retido em seu parênquima (DRIESSEN et al, 2001).…”
Section: Resultsunclassified
“…A PVC é um importante parâmetro de monitorização nas mais diversas situações clínicas (IMPERATORE et al, 2002;ONDA et al, 2003) e experimentais (PITTARD & VUCEVIC, 1998;DRIESSEN et al, 1999;SEZAI et al, 1999;CASTA et al, 2000;ERB et al, 2000;DRIESSEN et al, 2001;KUMAR, SOBTI & SINGH, 2001;LICK et al, 2001;LOZANO, CASTRO & RODRIGO, 2001;WATTERS et al, 2001;WIESENACK et al, 2001;VOSS et al, 2002). AMAR et al (2001) citam que pacientes submetidos a procedimentos cirúrgicos não cardíacos freqüentemente requerem monitoração por PVC para se obter informações acerca do estado de volume circulante e função cardíaca.…”
Section: Introductionunclassified